Legal basis for Corona lockdown worldwide : The case in Malaysia - Zulhuda, Sonny (2020)
This presentation focuses on the measures of restricted movement taken by the government of Malaysia during Covid-19 Pandemic. However, the discussion focuses on the legal aspects including the laws used as the basis of the Movement Control Order (RMO).